Large scale selective laser melting : study of the effects and removal of spatter by the inert gas flow - Ahmad Anwar (2019)
In commercial Selective Laser Melting (SLM) machines, the removal of spatter particles and other undesired by-products is performed by pumping inert gas unidirectionally over the powder bed. However, traces of deposited spatter which are darker in contrast as compared to the fresh powder are often observed during the SLM process. The effectiveness of the inert gas flow in transporting spatter particles was identified as a critical hindrance in the expansion of the powder bed area. With respect to the SLM machines produced by SLM Solutions Group AG (Lubeck, Germany), the powder bed width for all the current machine variants is limited to 280 mm along the x axis. In this thesis, studies on the effects of spatter particles, their distribution on the powder bed and the effectiveness of the inert gas flow, which were done experimentally and with the use of simulations, are presented. Firstly, Analysis of Variance (ANOVA) was applied to statistically reveal that parts of higher Ultimate Tensile Strength (UTS) was significantly obtained when laser scanning against the gas flow, at higher gas flow velocity and when scanning close to the outlet. Video evidence provided by a high-speed camera successfully captured more sparks when scanning in the direction of the gas flow. The sparks were attributed to the burning of spatter particles which were blown into the path of the laser beam by the gas flow. Following this, the spatter mass and size distributions on the powder bed, downstream of the laser-scanned sites were experimentally evaluated to establish the ground truth. Insights into the computations of the Stokes number (Stk) revealed an exponential decay with respect to the distance travelled by the spatter particles suspended in the gas flow. For the first time, the investigations elucidated the limitations in the effectiveness of the inert gas flow in removing spatter beyond the 280 mm limit. Finally, simulations of spatter particles under the influence of the inert gas flow were conducted using Computational Fluid Dynamics (CFD) and the Discrete Phase Model (DPM) for particle tracking. The effects of vapour driven entrainment on spatter ejections were considered. Despite not accounting for the full complexities of the multi-physics phenomena during SLM, good agreement was achieved with the earlier established experimental data on the mass and size distributions.